UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPSI MELALUI MODEL PEMBELAJARAN READ ANSWER DISCUSS EXPLAIN CREATE PADA SISWA KELAS VA SDN RAWAMANGUN 12 PAGI - Mochammad Hanif Rachman; Gusti Yarmi; Imaningtyas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve students' descriptive text writing skills in Indonesian language learning by implementing the Read Answer Discuss Explain Create learning model at SDN Rawamangun 12 Pagi, East Jakarta. This study is a classroom action research conducted in two cycles using the Kemmis and McTaggart model, which includes the planning, implementation, observation, and reflection stages. Each cycle is conducted in three meetings. The research subjects involved 32 fifth grade students in the 2025/2026 academic year consisting of 16 female students and 16 male students. Participants in this study were class VA teachers as collaborators or observers and colleagues who also helped. Data collection techniques through observation, interviews, documentation, and field notes. The results of the study showed an increase in students' descriptive text writing skills from 31% in cycle I to 94% in cycle II. These findings indicate that the use of the Read Answer Discuss Explain Create learning model is effective in improving students' descriptive text writing skills in Indonesian language learning.